Clinical grade medical device technologies for interventional cardivascular magnetic resonance imaging procedures - Yıldırım, Dursun Korel. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2021., 2021)
Magnetic Resonance Imaging (MRI) is a promising candidate against X-ray fluoroscopy for the image-guidance of minimally invasive procedures thanks to its ion izing radiation-free, exquisite soft tissue contrast and ability of 3D real-time imaging in arbitrary planes. However, interventional MRI (iMRI) is hampered by the lack of clinical grade MRI-compatible interventional devices. In this thesis study, first, a low profile iMRI device fabrication method was introduced by modifying the conductive ink printing method which was previously introduced by our group. Next, three most fundamental iMRI device designs including a 20 G active iMRI needle, a 0.035” outer di ameter metallic active iMRI guidewire and a 6 FR, MRI-safe, metallic braided catheter were successfully introduced to expand interventional cardiovascular MRI applications. Electromagnetic simulation tools were employed to optimize the device radio frequency (RF) antenna geometry for optimal device visibility, and to assess RF-safety of iMRI devices. Proposed iMRI device designs were prototyped using biocompatible materials. In-vitro mechanical, RF-induced heating and MRI visibility performance of the proto types were tested per international medical device test standards. In-vivo mechanical and MRI visibility tests were performed in swine per local animal study regulations. Test results were compared to commercially available equivalents. RF-induced temper ature rise of all three prototypes remained within clinically acceptable limits. Active iMRI needle and active iMRI guidewire prototypes were clearly visible during in-vitro and in-vivo tests. All prototypes demonstrated comparable mechanical performance with commercially available equivalents. Proposed iMRI device designs will meet the most urgent need in the iMRI field enabling a broad range of iMRI applications.|Keywords : interventional MRI, active device design, active iMRI needle, active iMRI guidewire, CMR-safe metal braided catheter.
Keywords: Interventional radiology.; Magnetic resonance imaging.